Avaliação da dor pós-operatória do tratamento endodôntico em pacientes com Diabetes Mellitus Tipo 2 – Um Ensaio Clínico Controlado. - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
This study aimed to evaluate the occurrence of postoperative pain in patients with type 2 diabetes mellitus (DM), after endodontic treatment, from a controlled, parallel and blinded clinical trial. The sample size consisted of 80 (eighty) adult patients with indication for endodontic treatment in permanent teeth, with partial intervention data from 20 patients with DM in the experimental group and 45 patients without DM in the control group. The research was carried out in three stages: consultation for baseline collection, endodontic treatment in a single session in both groups and collection of the outcome. In the instrumentation protocol, the WaveOne® Gold system was used, then root canal filling with gutta percha and resin cement was performed, followed by the temporary restoration of the dental element. Postoperative pain assessment was performed by another member of the team, blind to the groups, in which the pain intensity experienced by the patient was recorded at intervals of 6, 12, 24 and 72 hours after endodontic treatment, using two scales pain: discrete numerical (NRS) and ordinal verbal description (VRS). The partial results showed that the mean glycemia and glycated hemoglobin for the patients in the control group were 97.91 mg / dl and 5.10%, respectively, while in the experimental group with DM these values were 147.79 mg / dl and 8.02%, for this same group, the prevalence of postoperative pain was identified in 13 patients (56.52%) in the first 6 hours, in 9 (39.13%) patients in 12 hours, 8 (34.78% ) in 24 hours and only 5 patients (21.73%) in 72 hours; in the control group, this prevalence in the 6h interval was detected in 24 patients (61.53%), in 12h in 18 (46.15%), in 24h in 11 (28.20%) and in 72h, 6 patient (15 , 38%) reported some type of pain.The occurrence and intensity of postoperative pain in patients with DM after endodontic treatment at intervals of 6, 12, 24 and 72 hours showed lower absolute and relative values compared to the control group.
Keywords: Endodontia; Diabetes Mellitus; Tratamento endodôntico; Descrição verbal ordinal; Dor pós-operatória; CIÊNCIAS DA SAÚDE: ODONTOLOGIA; Diabetes Mellitus; Dor pós-operatória; Endodontia